The powers of war and peace : the constitution and foreign affairs after 9/11 - Yoo, John (University of Chicago Press, 2005)
John Yoo examines the constitutional framework for decisions about foreign affairs, particularly the powers of war and peace. He points out that from Truman and Korea to Clinton's intervention in Kosovo, US presidents have had to act decisively on the world stage without a declaration of war.